Ammonite and inoceramid bivalve extinction patterns in Cretaceous/Tertiary boundary sections of the Biscay region (southwestern France, northern Spain) - Ward, P; Kennedy, W; Macleod, K; Mount, J (1991)
Cretaceous/Tertiary boundary sections located in the Biscay region of southwestern France and northern Spain are among the most complete of all known land-based sequences across this boundary. New collections of ammonites and inoceramid bivalves from five localities show quite distinct extinction patterns for these two groups of characteristic Cretaceous molluscs: from eight to ammonite species extend into the latest Cretaceous, and possibly to the boundary. In contrast, inoceramid bivalve diversity gradually diminished from a minimum of six species in the early Maastrichtian to zero at the beginning of the late Maastrichtian, when they were replaced by the cryptic pteriomorph Tenuipteria. Extinction of typical inoceramids well before the end of the Maastrichtian is supported by data from other regions, indicating that it was a global rather than local phenomenon. -Authors